Acculturation and cigarette smoking in Hispanic women: A meta-analysis. Issue 1 (2nd January 2016) - Kondo, Karli K.; Rossi, Joseph S.; Schwartz, Seth J.; Zamboanga, Byron L.; Scalf, Carissa D.
ABSTRACT: The present study was a random-effects model meta-analysis of 26 studies published between 1990 and 2010 ( k  = 32; n  = 39, 777) that (a) examined the association between acculturation and cigarette smoking in Hispanic women and (b) evaluated age, national origin, and measure and dimensionality (unidimensional vs. bidimensional) of acculturation as moderating variables. Results indicate a strong positive relationship and suggest larger effects of acculturation on cigarette smoking in women of Mexican descent as compared with women originating from other Latin American countries for current and lifetime smoking, as well as smoking overall. The effect of acculturation on cigarette smoking was larger in adults as compared with adolescents for current smoking and smoking overall. Few differences in effect size by measure or dimensionality of acculturation emerged. Results are discussed with regard to implications for future research and the measurement of acculturation.